Shooting down moths: how foreign plaintiffs are denied access in U.S. courts - Crivellaro, Jacopo (Civil Procedure Review, 2011)
This author considers the recent trend of preventing foreigners from accessing United States federal courts through the heightening of pleading standards and the reinvigorated use of the forum non conveniens doctrine. The landmark Supreme Court case of Bell Atlantic v Twombly has raised the requirements for a plaintiff to survive a 12(b)(6) motion to dismiss for failure to state a claim. This is particularly troublesome for foreign plaintiffs who will have to gather sufficient information to satisfy the standard before having the benefit of discovery. Sinochem International v Malaysia International Shipping strengthened the application of the forum non conveniens doctrine by permitting federal courts to dismiss cases before considering issues of personal or subject matter jurisdiction. On the other hand, the two recent judgments of the Supreme Court, Nicastro v McIntyre and Goodyear v Brown restricted general and specific jurisdiction over foreign plaintiffs. The unexpected consequence of restricting foreign access to US courts and limiting suits against foreign defendants might homologize the US judicial system and demagnetize its appeal for foreign litigants.